2006
DOI: 10.1177/1721727x0600400204
|View full text |Cite
|
Sign up to set email alerts
|

Cytokines Mediating Inflammation in a Model of Secondary Immunodeficiency in Wistar Rats: Immunomodulation Triggered by Thymomodulin

Abstract: We have previously demonstrated in a rat model of immunodeficiency, an increase in the number of yo T cells in the gut lamina propria and in the number of CD8aa+, CD25+, y8+ subpopulations of intestinal intraepithelial lymphocytes (iIEL). The increased percentage of CD8aa+ iIEL that express CD25 indicates inflammation. The present study confirms the existence of an inflammatory process in the immunodeficient animals (R21) that is not detectable at the histological level but is characterized by an increase ofth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…The iIEL gd+T cells population co-express CD8a and CD25 as seen by cytometry (Olmos et al, 2004). Besides, they also co-express the cytokine TNF-a localized in LP and in the IE, (Delettieres et al, 2004;Olmos et al, 2006), accompanied by an increase of the pro-inflammatory cytokine TNF-a in intestinal lavage from animals after re-feeding indicating the presence of an inflammatory process (Olmos et al, 2006). Moreover, the gd T cell population co-express CCL25 differing in percentage distribution in the mucosal villi (Calabrese et al, 2007).…”
Section: Introductionmentioning
confidence: 93%
“…The iIEL gd+T cells population co-express CD8a and CD25 as seen by cytometry (Olmos et al, 2004). Besides, they also co-express the cytokine TNF-a localized in LP and in the IE, (Delettieres et al, 2004;Olmos et al, 2006), accompanied by an increase of the pro-inflammatory cytokine TNF-a in intestinal lavage from animals after re-feeding indicating the presence of an inflammatory process (Olmos et al, 2006). Moreover, the gd T cell population co-express CCL25 differing in percentage distribution in the mucosal villi (Calabrese et al, 2007).…”
Section: Introductionmentioning
confidence: 93%
“…Although, some studies have reported that high doses of immunostimulants in combination with vaccines can be immunosuppressive (LOGAMBAL & MICHAEL 2000). Some immunostimulatory peptides have been extracted from the thymus gland and have been used to enhance the resistance to pathogens or tumors and retardation of immune senescence in animal models (RAA 1996, OLMOS et al 2006. Thymomodulin is a calf thymus acid lysate derivative, composed of several peptides with a molecular weight range of 1-10KD, with capacity to modulate bone marrow stem cell proliferation and differentiation (KOUTTAB et al 1989), enhance the phagocytosis in rat macrophages and human polymorphonuclear cells in vitro (BRAGA et al 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Thymomodulin is a calf thymus acid lysate derivative, composed of several peptides with a molecular weight range of 1-10KD, with capacity to modulate bone marrow stem cell proliferation and differentiation (KOUTTAB et al 1989), enhance the phagocytosis in rat macrophages and human polymorphonuclear cells in vitro (BRAGA et al 1993). Thymomodulin has evidenced therapeutic action to counter the alterations in cytokine expression induced by an immunodeficiency model in rats (OLMOS et al 2006). Nevertheless, up to date, thymomodulin potential as immunostimulant for fish has not been addressed.…”
Section: Introductionmentioning
confidence: 99%
“…NCC is a chronic inflammation which potentially leads to the development of neoplastic lesions because it results in parasite-modulated host immune responses, release of endogenous carcinogens like nitric oxide in the brain, and DNA damage through genetic intervention. Also, NCC has recently been associated with other local malignant tumors, particularly glioblastoma multiforme, and also some hematological malignancies (94,95).…”
Section: Parasites and Cancermentioning
confidence: 99%